SEPTEMBER 11, TEN MONTHS LATER - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 2002)
In the months just following September 11, 2001, it was too soon to make an accurate evaluation of insurance claims, whether for human or financial losses. Ten months later, the author tries to outline the overall dimensions of the tragedy. Since last September, our lives have been irreversibly changed. In our personal life, we have had to confront a spectrum of emotions, from horror to admiration for heroic efforts. In the business milieu, many firms have been forced to retum to basics in their techniques and procedures. In the insurance field, the terrorist acts of September 11 actually caused the most catastrophic losses ever experienced by property and casualty insurers. Add in the impact of strong rate increases and it is easy to see why insurers and reinsurers have been forced to go back to basic rules in underwriting for large risks. The fateful date also has many lessons to teach us about new approaches to risk management; building codes; and the need for governments and industry to cooperate in finding financial solutions to cover mega-terrorist losses.